Primary prevention of childhood obesity: views from primary care. (4th April 2011) - Redsell, S; Atkinson, P; Nathan, D; Siriwardena, N; Swift, J; Glazebrook, C
Abstract : Introduction: Childhood obesity prevalence has increased significantly, yet primary risk factors are known and early prevention is possible. This study (a) explored parents' beliefs concerning their infant's size, growth and feeding and their receptiveness to intervention for those identified as at risk and (b) examined UK primary care practitioners' views and practice in relation to the identification and management of infants at risk of obesity. This study focuses on professionals. Methods: Informed consent was provided by parents (n=38) attending focus groups in six localities in the East Midlands, UK, selected for advantage/disadvantage. Practitioners working in these areas completed a brief survey, which included a validated measure (Obesity Risk Knowledge-10 scale) (n=118), and participated in telephone interviews (n=48). Qualitative data were audio-recorded, transcribed verbatim and subjected to thematic analysis. Survey data were analysed using non-parametric statistics. Results: Infant feeding and the prevention of obesity were principle qualitative themes. Parents described obesogenic infant feeding practices and reported inconsistencies in practitioners' advice. General practitioners (GP) (n=12) and Practice Nurses (n=6) believed feeding advice was health visitors' responsibility, relied on experiential knowledge rather than evidence to support advice and valued the practitioner-patient relationship over best practice. Health Visitors (n=20) and their team (n=10) supported best practice but identified barriers to implementation. Obesity prevention was seen as important by all professional groups but practitioners wanted more guidance and training. All survey participants had been consulted for advice about infant feeding. Knowledge about health risks associated with obesity differed significantly between practitioner groups (X2=26.7, df=3, p<0.001). GPs (n=52) were significantly more knowledgeable about the risks of obesity than the other groups. In the group as a whole, knowledge was unrelated to confidence in relation to feeding advice and those with better knowledge were consulted less frequently about infant feeding (r=-0.34, n=114, p<0.001). Conclusion: This study revealed potentially modifiable barriers to intervention with parents of infants identified as at risk of obesity. The priorities of supporting parents to improve infant feeding practices, improving practitioners' knowledge and better team working will inform the development of a complex intervention to address this area of practice.